Pengaruh Dukungan Manajemen Dan Adaptabilitas Terhadap Resiliensi Kerja Guru Dan Karyawan Di Masa Pandemi Covid-19 (Studi Kasus Yayasan Insan Mulia Malang) - Choiriah Indah Kusumawati; Pardiman Pardiman; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to analyze: the effect of management support and adaptability on the work resilience of teachers and employees during the covid-19 pandemic, the direct influence of management support on the work resilience of teachers and employees during the covid-19 pandemic, its direct influence on the work resilience of teachers and employees during the covid-19 pandemic. direct adaptability to the work resilience of teachers and employees during the COVID-19 pandemic. The sample in this study used the entire population, namely teachers and employees yayasan insan mulia malang Foundation which amounted to 51 people. The results of this study indicate:  management support and adaptability have a simultaneous effect on work resilience, management support has no partial effect on work resilience, adaptability has a partial effect on work resilience. Keywords: Management Support, Adaptability and Work Resilience